Przekształć wyrażenia do najprostszej postaci:

4 + (5x – 3y + 2) -3(4x – 2y +1) =

6ab – (-3ab+a-4b+1) +2(ab – 4a + 5b -3) =

-4x + (5x -7) -2(x-1) +3(-x-2) – (-3x+5) =

2. Wiedząc, że A=4x+2y-1 i B= 4x-2y+1 oblicz:

a) A+B

b) B-A

c) 2 – A – 2B



Odpowiedź :

SoeCru

Zad. 1

4+(5x-3y+2)-3(4x-2y+1) =4+5x-3y+2-12x+6y-3=5x-12x-3y+6y+4+2-3=-7x+3y+3

6ab-(-3ab+a-4b+1)+2(ab-4a+5b-3)=6ab+3ab-a+4b-1+2ab-8a+10b-6=

=-a-8a+4b+10b+6ab+3ab+2ab-6=-9a+14b+11ab-7

-4x+(5x-7)-2(x-1)+3(-x-2)-(-3x+5)=-4x+5x-7-2x+2-3x-6+3x-5=

=-4x+5x-2x-3x+3x-7+2-6-5=-x-16

Zad. 2

a) A+B=(4x+2y-1)+(4x-2y+1)=4x+4x=8x

b) B-A=(4x-2y+1)-(4x+2y-1)=4x-2y+1-4x-2y+1=-2y-2y+1+1=-4y+2

c) 2-A-2B=2-(4x+2y-1)-2(4x-2y+1)=-4x-2y+1-8x+4y=-4x-8x-2y+4y+1=-12x+2y+1